Immune responses to resistance exercise performed over either 3 consecutive or non-consecutive days - Huang, Junli (2016)
Purpose: This study investigates the body’s immune responses to resistance exercise (RE) that were performed over either 3 consecutive days (C) or non-consecutive days (NC).